Asynchronous normal regional left ventricular function assessed by speckle tracking echocardiography - Lindqvist, P.; Borgström, E.; Gustafsson, U.; Mörner, S.; Henein, M.Y. (International journal of cardiology, 2009)
Speckle tracking echocardiography (STE) is an angle independent method with high temporal resolution, which offers quantification of regional left ventricular (LV) wall motion. We studied radial and longitudinal LV wall motion by STE in healthy subjects with normal wall motion analysis (WMA) by eye-balling. Eighteen healthy subjects were studied. We acquired parasternal short and apical long axis projections to determine the basal, mid and apical radial and longitudinal functions. At each level we measured; (I) radial and longitudinal peak displacement and displacement at aortic valve closure (AVC) and (II) the time interval from the Q-wave to the AVC and peak displacement. WMA indicated normal wall motion in all subjects. The mean peak radial displacement varied in different segments (range 3.9–9.8 mm) with highest values in the mid-level (6.9 ± 1.5 mm), compared to basal level (5.9 ± 1.0 mm, p < 0.01) and apical level (5.4 ± 1.0 mm, p < 0.001). The time from Q-wave to AVC was 393 ms and in 89% of the analysed segments peak radial displacement occurred after AVC, thus mean peak radial displacement occurred 60 ms after AVC. The peak longitudinal amplitude was more synchronous with respect to AVC and with the highest amplitudes found in the two basal segments. In normal LV function, significant differences in peak displacement exist between segments at various LV levels using STE. In addition, in early diastole, significant discrepancy occurs between radial and longitudinal time of peak displacement, suggesting a shape change. Finally, while radial displacement was highest at mid-cavity level longitudinal displacement was highest at basal level.